Anti-aging and anti-yellowing foaming polyester material and preparation method thereof

By introducing components such as UV-resistant SEBS, flame-retardant and wear-resistant fillers and polymer wax into TPEE foaming materials, copolymerized grafting and mixing reactions, the melt strength and performance degradation of TPEE foaming materials at foaming temperature are solved. The problem is that the material's anti-aging, yellowing resistance, foaming and flame retardant properties are significantly improved.

CN119463424AActive Publication Date: 2025-02-18JIANGSU HESHILI NEW MATERIAL +1

Patent Information

Application Number
CN202411392743.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-18
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The melt strength of TPEE foaming materials decreases at the foaming temperature, resulting in uneven gas formation, and problems such as string holes and bubble cell rupture. At the same time, they lack oxidation resistance and yellowing resistance and flame retardant properties.

Method used

The materials are improved by using UV-resistant SEBS, flame-retardant and wear-resistant fillers and polymer waxes.

Benefits of technology

The anti-aging, yellowing resistance, foaming and flame retardant properties of TPEE foamed materials are significantly improved, and the problems of melt strength decline and performance degradation are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-aging and anti-yellowing foaming polyester material and a preparation method thereof, and relates to the technical field of polyester materials. The anti-aging and yellowing-resistant foamed polyester material is prepared from the following raw material components in parts by weight: 3 to 5 parts of anti-ultraviolet SEBS (Styrene-Ethylene-Butylene-Styrene), 3.6 to 7 parts of triethylamine, 4 to 6 parts of flame-retardant and wear-resistant filler, 100 parts of TPEE (Thermoplastic Polyether Ester Ether), 0.9 to 1.1 parts of polymer wax and 0.6 to 0.8 part of foaming agent, the anti-ultraviolet SEBS is obtained by copolymerizing and grafting an unsaturated benzophenone ultraviolet absorbent, SEBS and maleic anhydride; the flame-retardant and wear-resistant filler is obtained by mixing and reacting carboxylated nano silicon dioxide, pentaerythritol and phosphorus oxychloride; the polymer wax adopts EVA (Ethylene Vinyl Acetate) wax; azodicarbonamide is adopted as the foaming agent; the anti-aging and anti-yellowing foaming polyester material disclosed by the invention is relatively good in mechanical property, anti-aging property, flame retardant property and compression resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester materials, in particular to an anti-aging and yellowing resistant foamed polyester material and a preparation method thereof. Background Art

[0002] Thermoplastic polyester elastomer (TPEE) is a unique block copolymer, which consists of an aromatic polyester hard segment (crystalline phase) and an aliphatic polyester or polyether soft segment (continuous phase). It has the softness and elasticity of rubber and the rigidity and easy processing of thermoplastics. TPEE has attracted widespread attention due to its high mechanical strength, good elasticity, strong impact resistance, and excellent creep resistance, cold resistance, bending fatigue resistance, oil resistance, chemical resistance and solvent corrosion resistance. These characteristics make it widely used in a wide range of fields such as automotive parts, hydraulic hoses, cables and wires, sporting goods, construction and other fields.

[0003] As a new type of composite material that is lightweight, material-saving and has high specific strength, foam materials have been widely used in the fields of industry, agriculture, transportation, information technology, high-speed railways, and aerospace due to their excellent thermal insulation, sound insulation and cushioning properties. With the advancement of science and technology, the relevant scientific and technological achievements of foam materials have attracted great attention from scientific and technological personnel in the field of polymer processing.

[0004] TPEE foaming material aims to combine the excellent performance of TPEE and the advantages of foaming materials to form a new type of material with high strength, high elasticity, and the ability to effectively absorb stress and buffer vibration. However, the structural characteristics of TPEE itself determine that its resin melt has high fluidity and low melt strength. The melt strength will drop significantly at the foaming temperature, making it difficult to maintain gas in the resin to form uniform bubbles, resulting in problems such as string holes and bubble rupture.

[0005] To solve this problem, star block copolymer SEBS (styrene-ethylene / butylene-styrene) can be used to improve the melt strength of TPEE. SEBS has high physical cross-linking effect, high modulus and is not easy to degrade, so it has high melt strength. However, the lack of polar and reactive groups on the SEBS molecular chain limits its compatibility with TPEE. Combining SEBS and TPEE not only fails to form a more uniform pore structure, but also reduces the performance of TPEE.

[0006] In addition, in the design and production process of TPEE foam materials, factors such as anti-oxidation and yellowing resistance and flame retardancy need to be considered. Anti-oxidation and yellowing resistance are very important for extending the service life of materials and maintaining beautiful appearance, while flame retardancy is an essential safety requirement in many application fields (especially construction and vehicle interior parts).

[0007] Therefore, the applicant prepared an anti-aging and yellowing resistant foamed polyester material to solve the above problems. Summary of the invention

[0008] In order to solve the existing technical problems, the present invention provides an anti-aging and yellowing resistant foamed polyester material. The raw material components, measured by weight, include: 3 to 5 parts of anti-ultraviolet SEBS, 3.6 to 7 parts of triethylamine, 4 to 6 parts of flame retardant and wear-resistant fillers, 100 parts of TPEE, 0.9 to 1.1 parts of polymer wax, and 0.6 to 0.8 parts of foaming agent.

[0009] Furthermore, the anti-ultraviolet SEBS is obtained by copolymerization and grafting of unsaturated benzophenone ultraviolet absorber, SEBS and maleic anhydride.

[0010] Furthermore, the unsaturated benzophenone ultraviolet absorber is obtained by a mixed reaction of 2,4,4-trihydroxybenzophenone and acryloyl chloride.

[0011] Furthermore, the flame retardant and wear resistant filler is obtained by mixing carboxylated nano silicon dioxide, pentaerythritol and phosphorus oxychloride.

[0012] Furthermore, the carboxylated nano-silica is obtained by sequentially reacting silane coupling agent KH550, terephthalic acid and nano-silica.

[0013] Furthermore, the polymer wax is EVA wax.

[0014] Furthermore, the foaming agent is azodicarbonamide.

[0015] The present invention also provides an anti-aging and yellowing resistant foamed polyester material, comprising the following preparation steps: (1) Prepare the materials according to the following weight proportions: 3-5 parts of anti-ultraviolet SEBS, 3.6-7 parts of triethylamine, 2.5-3.5 parts of flame retardant and wear-resistant filler, 100 parts of TPEE, 0.9-1.1 parts of polymer wax, and 0.6-0.8 parts of foaming agent; (2) Under nitrogen protection, anti-ultraviolet SEBS and toluene were mixed in a mass ratio of 1:20-40, stirred at 500-900 rpm for 2-4 h, and then triethylamine and flame-retardant and wear-resistant fillers were added. Stirring was continued at 90 °C for 13-15 h, and the mixture was naturally cooled to room temperature and filtered. The mixture was washed with ethyl acetate and deionized water for 3-5 times in turn, and dried in a vacuum drying oven at 100 °C overnight to constant weight. The mixture was then placed in a high-speed mixer together with TPEE and EVA wax and stirred at 70 °C for 2-4 min. Then, azodicarbonamide, a foaming agent, was added, mixed evenly, and discharged. The mixture was then added to a single-screw extruder with a metering section temperature of 220-230 °C, a die temperature of 195 °C, and a screw speed of 60 rpm for extrusion. The mixture was cooled, pulled, and calendered into sheets.

[0016] Furthermore, the preparation method of the anti-ultraviolet SEBS is as follows: drying maleic anhydride in a vacuum drying oven at 120°C for more than 12 hours, first stirring and dissolving maleic anhydride, unsaturated benzophenone ultraviolet absorber, diisopropylbenzene peroxide, and acetone in a mass ratio of 1:1.2~1.4:0.09~0.11:10, and then evenly sprinkling it on the surface of SEBS powder with a mass of 90~100 times that of maleic anhydride, and then placing it in a high-speed mixer and stirring at 1000~2000rpm for 5min, setting the stirring temperature to 80°C, and after mixing, using a twin-screw extruder for extrusion, the temperatures of each zone of the extruder are set to 220, 245, 265, 285, and 270°C, respectively, and the screw speed is set to 40r / min.

[0017] Furthermore, the preparation method of the unsaturated benzophenone ultraviolet absorber is as follows: 1M / L sodium hydroxide aqueous solution and 2,4,4-trihydroxybenzophenone are mixed, and after complete dissolution at 300~500rpm, they are then stirred at 1200~1500rpm in an ice water bath, and acryloyl chloride is added dropwise, reacted for 1.5~2.5h, filtered, and an unsaturated benzophenone ultraviolet absorber is obtained; wherein the molar ratio of 2,4,4-trihydroxybenzophenone, acryloyl chloride, and sodium hydroxide is 1:0.9~1.1:1.

[0018] Furthermore, the preparation method of the flame retardant and wear-resistant filler is as follows: dispersing carboxylated nano-silicon dioxide in toluene at a mass of 20 to 40 times, then adding pentaerythritol at a mass of 0.5 to 0.6 times the mass of the carboxyl group in the carboxylated nano-silicon dioxide, stirring at 300 to 500 rpm for 20 to 40 minutes, then adding concentrated sulfuric acid at a mass of 0.2 to 0.4 times the mass of the carboxylated nano-silicon dioxide, heating and refluxing for 2 to 4 hours, filtering, washing with acetone and deionized water for 2 to 4 times in sequence, and placing at 80°C. The mixture was dried in an oven for 48 hours, and then mixed with phosphorus oxychloride, wherein the molar ratio of pentaerythritol to phosphorus oxychloride was 1:6-6.5. The mixture was heated to 80°C for reaction for 1.8-2.2 hours, and then heated to 110°C, and stirred at 1300-1700 rpm for reaction overnight until substantially no hydrogen chloride gas was generated. The mixture was then cooled to room temperature, filtered, and dried in a vacuum drying oven at 80°C to constant weight to obtain a flame retardant and wear resistant filler. During the filtration process, the mixture was washed with dichloromethane and ether for 3 times, respectively.

[0019] Furthermore, the preparation method of the carboxylated nano-silica is as follows: the nano-silica is ultrasonically dispersed in N,N-dimethylformamide with a mass of 20 to 40 times that of the nano-silica for 20 to 40 minutes, and then a KH550 hydrolyzate with a mass fraction of 6% is added, wherein the mass of the KH550 hydrolyzate is 1 to 2 times the mass of the nano-silica, and then the mixture is ultrasonically stirred for 5 hours, and then poured into deionized water with a mass of 50 to 100 times that of the nano-silica, and allowed to stand for 24 hours, filtered, dried in an oven at 120°C for 48 hours, and then naturally cooled to room temperature, and then dispersed in benzene with a mass of 40 to 60 times that of the nano-silica, and terephthalic acid with an equal mole of KH550 is added, and the temperature is raised to 85 to 95°C, and the mixture is continuously ultrasonically stirred for 1 to 2 hours, filtered, washed with acetone and deionized water for 2 to 4 times in sequence, and dried in an oven at 80°C for 48 hours to obtain carboxylated nano-silica.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The anti-aging and yellowing resistant foamed polyester material of the invention comprises the following steps: firstly, unsaturated benzophenone ultraviolet absorber, SEBS and maleic anhydride are copolymerized and grafted to obtain anti-ultraviolet SEBS; then, carboxylated nano silicon dioxide, pentaerythritol and phosphorus oxychloride are mixed and reacted to obtain flame retardant and wear-resistant filler; finally, anti-ultraviolet SEBS, triethylamine, flame retardant and wear-resistant filler, TPEE, polymer wax and foaming agent are mixed and reacted to obtain the anti-aging and yellowing resistant foamed polyester material; wherein, the unsaturated benzophenone ultraviolet absorber is obtained by mixed reaction of 2,4,4-trihydroxybenzophenone and acryloyl chloride; and the carboxylated nano silicon dioxide is obtained by sequentially reacting silane coupling agent KH550, terephthalic acid and nano silicon dioxide.

[0021] Firstly, unsaturated benzophenone UV absorbers and maleic anhydride are copolymerized and grafted with SEBS, maleic anhydride and unsaturated benzophenone UV absorbers are introduced into the SEBS molecular chain, and polar groups and UV absorbers are introduced into the SEBS molecular chain to enhance the UV oxidation resistance of SEBS and its compatibility with TPEE, thereby enhancing the foaming performance, mechanical properties and UV oxidation resistance of TPEE foaming materials.

[0022] Secondly, carboxylated nano-silica, pentaerythritol and phosphorus oxychloride are mixed and reacted to obtain a flame retardant and wear-resistant filler. The hydroxyl groups on pentaerythritol react with carboxylated nano-silica and phosphorus oxychloride respectively to form a layer of chloropentaerythritol phosphate derivative on the surface of carboxylated nano-silica. The presence of nano-silica can promote the decomposition of chloropentaerythritol phosphate derivative at high temperature and accelerate the formation of phosphide, thereby improving the carbonization efficiency. At the same time, nano-silica and chloropentaerythritol phosphate derivative work together to form a denser physical barrier and carbon layer during combustion, which effectively prevents the transfer of heat and oxygen and reduces the generation of combustible gas, thereby improving the flame retardant properties of the flame retardant and wear-resistant filler.

[0023] Subsequently, anti-ultraviolet SEBS, triethylamine, flame retardant and wear-resistant filler, TPEE, polymer wax and foaming agent are mixed and reacted to obtain anti-aging and yellowing resistant foamed polyester material; adding anti-ultraviolet SEBS to TPEE can effectively improve the anti-ultraviolet performance and foaming performance of the anti-aging and yellowing resistant foamed polyester material; adding flame retardant and wear-resistant filler, on the one hand, provides a nucleating agent for the foaming of polyester material to obtain a more uniform and more uniform pore structure, thereby ensuring the mechanical properties of the anti-aging and yellowing resistant foamed polyester material; wherein, the flame retardant and wear-resistant filler, Anti-ultraviolet SEBS and triethylamine are mixed, and then TPEE, polymer wax and foaming agent are added and mixed. The chlorine on the chlorinated pentaerythritol phosphate derivative on the flame retardant and wear-resistant filler reacts with the hydroxyl on the anti-ultraviolet SEBS to graft the flame retardant and wear-resistant filler firmly onto the anti-ultraviolet SEBS, so that it is evenly dispersed in TPEE, thereby enhancing the anti-ultraviolet performance and flame retardancy of the anti-aging and yellowing resistant foamed polyester material, while enhancing the foaming performance of the anti-aging and yellowing resistant foamed polyester material, thereby enhancing the mechanical properties of the anti-aging and yellowing resistant foamed polyester material. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.

[0025] The TPEE used in the examples and comparative examples of the present invention is TPEE resin-H63DMG; the SEBS uses SEBS of model YH501 produced by Baling Petrochemical Co., Ltd.; and the EVA wax is obtained from Beijing Dongfang Petrochemical Co., Ltd.

[0026] The following table shows the properties of the TPEE resin: Example 1

[0027] A method for preparing an anti-aging and yellowing resistant foamed polyester material, the preparation steps are as follows: (1) Prepare the materials according to the following weight proportions: 3 parts of anti-ultraviolet SEBS, 3.6 parts of triethylamine, 4 parts of flame retardant and wear-resistant filler, 100 parts of TPEE, 0.9 parts of polymer wax, and 0.6 parts of foaming agent; (2) Under nitrogen protection, anti-ultraviolet SEBS and toluene were mixed in a mass ratio of 1:20 and stirred at 500 rpm for 2 h. Subsequently, triethylamine and flame-retardant and wear-resistant fillers were added and stirred at 90 °C for 13 h. After natural cooling to room temperature, the mixture was filtered and washed with ethyl acetate and deionized water for 3 times in sequence. The mixture was dried in a vacuum drying oven at 100 °C overnight to constant weight. Subsequently, the mixture was put into a high-speed mixer together with TPEE and EVA wax and stirred at 70 °C for 2 min. Then, azodicarbonamide, a foaming agent, was added and mixed evenly. The mixture was discharged and continued to be added into a single-screw extruder with a metering section temperature of 220 °C, a die head temperature of 195 °C and a screw speed of 60 rpm for extrusion. The mixture was cooled, pulled and calendered into sheets.

[0028] Furthermore, the preparation method of the anti-ultraviolet SEBS is as follows: drying maleic anhydride in a vacuum drying oven at 120°C for more than 12 hours, first stirring and dissolving maleic anhydride, unsaturated benzophenone ultraviolet absorber, diisopropylbenzene peroxide, and acetone in a mass ratio of 1:1.2:0.09:10, and then evenly sprinkling it on the surface of SEBS powder with a mass of 90 times that of maleic anhydride, and then placing it in a high-speed mixer and stirring it at 1000rpm for 5 minutes, setting the stirring temperature to 80°C, and after mixing, using a twin-screw extruder for extrusion, the temperatures of each zone of the extruder are set to 220, 245, 265, 285, and 270°C, respectively, and the screw speed is set to 40r / min.

[0029] Furthermore, the preparation method of the unsaturated benzophenone ultraviolet absorber is as follows: 1M / L sodium hydroxide aqueous solution and 2,4,4-trihydroxybenzophenone are mixed, and after complete dissolution at 300rpm, they are stirred at 1200rpm in an ice water bath, and acryloyl chloride is added dropwise, reacted for 1.5h, and filtered to obtain an unsaturated benzophenone ultraviolet absorber; wherein the molar ratio of 2,4,4-trihydroxybenzophenone, acryloyl chloride, and sodium hydroxide is 1:0.9:1.

[0030] Furthermore, the preparation method of the flame retardant and wear-resistant filler is as follows: dispersing carboxylated nano-silica in toluene 20 times its mass, then adding pentaerythritol 0.5 times the amount of carboxyl in the carboxylated nano-silica, stirring at 300 rpm for 20 minutes, then adding concentrated sulfuric acid 0.2 times the mass of the carboxylated nano-silica, heating and refluxing for 2 hours, filtering, washing with acetone and deionized water twice in sequence, placing in an 80°C oven to dry for 48 hours, and then mixing with phosphorus oxychloride, wherein the molar ratio of pentaerythritol to phosphorus oxychloride is 1:6, heating to 80°C for reaction for 1.8 hours, then heating to 110°C, stirring at 1300 rpm for reaction overnight until substantially no hydrogen chloride gas is generated, and then cooling to room temperature, filtering and placing in a vacuum drying oven at 80°C to dry to constant weight to obtain a flame retardant and wear-resistant filler; wherein, during the filtration process, washing with dichloromethane and ether three times respectively.

[0031] Furthermore, the preparation method of the carboxylated nano-silica is as follows: the nano-silica is ultrasonically dispersed in N,N-dimethylformamide (20 times its mass) for 20 minutes, and then a KH550 hydrolyzate with a mass fraction of 6% is added, wherein the mass of the KH550 hydrolyzate is 1 times the mass of the nano-silica, and then the mixture is ultrasonically stirred for 5 hours, and then poured into deionized water (50 times the mass of the nano-silica), allowed to stand for 24 hours, filtered, dried in an oven at 120°C for 48 hours, and then naturally cooled to room temperature, and then dispersed in benzene (40 times the mass of the nano-silica), and terephthalic acid (equimolar to KH550) is added, the temperature is raised to 85°C, and the mixture is ultrasonically stirred for 1 hour, filtered, washed twice with acetone and deionized water in sequence, and dried in an oven at 80°C for 48 hours to obtain carboxylated nano-silica. Example 2

[0032] A method for preparing an anti-aging and yellowing resistant foamed polyester material, the preparation steps are as follows: (1) Prepare the materials according to the following weight proportions: 4 parts of anti-ultraviolet SEBS, 5.3 parts of triethylamine, 5 parts of flame retardant and wear-resistant filler, 100 parts of TPEE, 1 part of polymer wax, and 0.7 parts of foaming agent; (2) Under nitrogen protection, anti-ultraviolet SEBS and toluene were mixed in a mass ratio of 1:30 and stirred at 700 rpm for 3 h. Subsequently, triethylamine and flame-retardant and wear-resistant fillers were added and stirred at 90 °C for 14 h. After natural cooling to room temperature, the mixture was filtered and washed with ethyl acetate and deionized water for 4 times in sequence. The mixture was dried in a vacuum drying oven at 100 °C overnight to constant weight. Subsequently, the mixture was put into a high-speed mixer together with TPEE and EVA wax and stirred at 70 °C for 3 min. Then, azodicarbonamide, a foaming agent, was added and mixed evenly. The mixture was discharged and continued to be extruded into a single-screw extruder with a metering section temperature of 225 °C, a die head temperature of 195 °C and a screw speed of 60 rpm. The mixture was cooled, pulled and calendered into sheets.

[0033] Furthermore, the preparation method of the anti-ultraviolet SEBS is as follows: drying maleic anhydride in a vacuum drying oven at 120°C for more than 12 hours, first stirring and dissolving maleic anhydride, unsaturated benzophenone ultraviolet absorber, diisopropylbenzene peroxide, and acetone in a mass ratio of 1:1.3:0.1:10, and then evenly sprinkling it on the surface of SEBS powder with a mass of 95 times that of maleic anhydride, and then placing it in a high-speed mixer and stirring it at 1500rpm for 5 minutes, setting the stirring temperature to 80°C, and after mixing, using a twin-screw extruder for extrusion, the temperatures of each zone of the extruder are set to 220, 245, 265, 285, and 270°C, respectively, and the screw speed is set to 40r / min.

[0034] Furthermore, the preparation method of the unsaturated benzophenone ultraviolet absorber is as follows: 1M / L sodium hydroxide aqueous solution and 2,4,4-trihydroxybenzophenone are mixed, and after complete dissolution at 400rpm, they are stirred at 1400rpm in an ice water bath, and acryloyl chloride is added dropwise, reacted for 2h, and filtered to obtain an unsaturated benzophenone ultraviolet absorber; wherein the molar ratio of 2,4,4-trihydroxybenzophenone, acryloyl chloride, and sodium hydroxide is 1:1:1.

[0035] Furthermore, the preparation method of the flame retardant and wear-resistant filler is as follows: dispersing carboxylated nano-silica in toluene 30 times its mass, then adding pentaerythritol 0.55 times the amount of carboxyl in the carboxylated nano-silica, stirring at 400 rpm for 30 minutes, then adding concentrated sulfuric acid 0.3 times the mass of the carboxylated nano-silica, heating and refluxing for 3 hours, filtering, washing with acetone and deionized water three times in sequence, placing in an 80°C oven to dry for 48 hours, and then mixing with phosphorus oxychloride, wherein the molar ratio of pentaerythritol to phosphorus oxychloride is 1:6.3, heating to 80°C for reaction for 2 hours, then heating to 110°C, stirring at 1500 rpm for reaction overnight until substantially no hydrogen chloride gas is generated, and then cooling to room temperature, after suction filtration, placing in a vacuum drying oven at 80°C to dry to constant weight, to obtain a flame retardant and wear-resistant filler; wherein, during the suction filtration process, washing with dichloromethane and ether three times respectively.

[0036] Furthermore, the preparation method of the carboxylated nano-silica is as follows: the nano-silica is ultrasonically dispersed in N,N-dimethylformamide (30 times its mass) for 30 minutes, and then a KH550 hydrolyzate with a mass fraction of 6% is added, wherein the mass of the KH550 hydrolyzate is 1.5 times the mass of the nano-silica, and then the mixture is ultrasonically stirred for 5 hours, and then poured into deionized water (80 times the mass of the nano-silica), allowed to stand for 24 hours, filtered, dried in an oven at 120°C for 48 hours, and then naturally cooled to room temperature, and then dispersed in benzene (50 times the mass of the nano-silica), and terephthalic acid (equimolar to KH550) is added, the temperature is raised to 90°C, and the mixture is ultrasonically stirred for 1.5 hours, filtered, washed with acetone and deionized water three times in sequence, and dried in an oven at 80°C for 48 hours to obtain carboxylated nano-silica. Example 3

[0037] A method for preparing an anti-aging and yellowing resistant foamed polyester material, the preparation steps are as follows: (1) Prepare the materials according to the following weight proportions: 5 parts of anti-ultraviolet SEBS, 7 parts of triethylamine, 6 parts of flame retardant and wear-resistant filler, 100 parts of TPEE, 1.1 parts of polymer wax, and 0.8 parts of foaming agent; (2) Under nitrogen protection, anti-ultraviolet SEBS and toluene were mixed in a mass ratio of 1:40, stirred at 900 rpm for 4 h, and then triethylamine and flame retardant and wear-resistant filler were added. Stirring was continued at 90 °C for 15 h. After natural cooling to room temperature, the mixture was filtered and washed with ethyl acetate and deionized water for 5 times in sequence. The mixture was dried in a vacuum drying oven at 100 °C overnight to constant weight. The mixture was then put into a high-speed mixer together with TPEE and EVA wax and stirred at 70 °C for 4 min. Then, azodicarbonamide, a foaming agent, was added, mixed evenly, and discharged. The mixture was then added into a single screw extruder with a metering section temperature of 230 °C, a die head temperature of 195 °C, and a screw speed of 60 rpm for extrusion. The mixture was cooled, pulled, and calendered into sheets.

[0038] Furthermore, the preparation method of the anti-ultraviolet SEBS is as follows: drying maleic anhydride in a vacuum drying oven at 120°C for more than 12 hours, first stirring and dissolving maleic anhydride, unsaturated benzophenone ultraviolet absorber, diisopropylbenzene peroxide, and acetone in a mass ratio of 1:1.4:0.11:10, and then evenly sprinkling it on the surface of SEBS powder with a mass of 100 times that of maleic anhydride, and then placing it in a high-speed mixer and stirring it at 2000rpm for 5 minutes, setting the stirring temperature to 80°C, and after mixing, using a twin-screw extruder for extrusion, the temperatures of each zone of the extruder are set to 220, 245, 265, 285, and 270°C, respectively, and the screw speed is set to 40r / min.

[0039] Furthermore, the preparation method of the unsaturated benzophenone ultraviolet absorber is as follows: 1M / L sodium hydroxide aqueous solution and 2,4,4-trihydroxybenzophenone are mixed, and after complete dissolution at 500rpm, they are stirred at 1500rpm in an ice water bath, and acryloyl chloride is added dropwise, reacted for 2.5h, and filtered to obtain an unsaturated benzophenone ultraviolet absorber; wherein the molar ratio of 2,4,4-trihydroxybenzophenone, acryloyl chloride, and sodium hydroxide is 1:1.1:1.

[0040] Furthermore, the preparation method of the flame retardant and wear-resistant filler is as follows: dispersing carboxylated nano-silica in toluene 40 times its mass, then adding pentaerythritol 0.6 times the amount of carboxyl in the carboxylated nano-silica, stirring at 500 rpm for 40 minutes, then adding concentrated sulfuric acid 0.4 times the mass of the carboxylated nano-silica, heating and refluxing for 4 hours, filtering, washing with acetone and deionized water 4 times in sequence, placing in an 80°C oven to dry for 48 hours, and then mixing with phosphorus oxychloride, wherein the molar ratio of pentaerythritol to phosphorus oxychloride is 1:6.5, heating to 80°C for reaction for 2.2 hours, then heating to 110°C, stirring at 1700 rpm for reaction overnight until substantially no hydrogen chloride gas is generated, and then cooling to room temperature, after suction filtration, placing in a vacuum drying oven at 80°C to dry to constant weight, to obtain a flame retardant and wear-resistant filler; wherein, during the suction filtration process, washing with dichloromethane and ether 3 times respectively.

[0041] Furthermore, the preparation method of the carboxylated nano-silica is as follows: the nano-silica is ultrasonically dispersed in N,N-dimethylformamide (40 times its mass) for 40 minutes, and then a KH550 hydrolyzate with a mass fraction of 6% is added, wherein the mass of the KH550 hydrolyzate is twice the mass of the nano-silica, and then the mixture is ultrasonically stirred for 5 hours, and then poured into deionized water (100 times the mass of the nano-silica), allowed to stand for 24 hours, filtered, dried in an oven at 120°C for 48 hours, and then naturally cooled to room temperature, and then dispersed in benzene (60 times the mass of the nano-silica), and terephthalic acid (equimolar to KH550) is added, the temperature is raised to 95°C, and the mixture is ultrasonically stirred for 2 hours, filtered, washed 4 times with acetone and deionized water in sequence, and dried in an oven at 80°C for 48 hours to obtain carboxylated nano-silica.

[0042] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that only UV-0, SEBS and maleic anhydride are blended and extruded to obtain UV-resistant SEBS; the remaining steps and ingredients are the same as those in Example 2.

[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that only unsaturated benzophenone ultraviolet absorber and SEBS are copolymerized and grafted to obtain anti-ultraviolet SEBS; the remaining steps and components are the same as those in Example 2.

[0044] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that UV-0 and SEBS are blended and extruded to obtain UV-resistant SEBS, and mercuric chloride and iodine are not introduced; the remaining steps and ingredients are the same as those in Example 2.

[0045] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that only nano-silicon dioxide, pentaerythritol and phosphorus oxychloride are mixed and reacted to obtain the flame-retardant and wear-resistant filler; the remaining steps and ingredients are the same as those in Example 2.

[0046] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that only carboxylated nano-silica and pentaerythritol phosphate are mixed and reacted to obtain a flame-retardant and wear-resistant filler; wherein the amount of pentaerythritol phosphate is 10 parts by mass; and the remaining steps and ingredients are the same as those in Example 2.

[0047] Comparative Example 6 The only difference between Comparative Example 6 and Example 2 is that only UV-0, triethylamine, flame retardant and wear-resistant filler, TPEE, polymer wax and foaming agent are mixed and reacted to obtain an anti-aging and yellowing resistant foamed polyester material; the remaining steps and ingredients are the same as those in Example 2.

[0048] Comparative Example 7 The only difference between Comparative Example 7 and Example 2 is that only anti-ultraviolet SEBS, triethylamine, nano titanium dioxide, pentaerythritol phosphate, TPEE, polymer wax, and foaming agent are mixed and reacted and then foamed to obtain an anti-aging and yellowing resistant foamed polyester material; wherein, the nano titanium dioxide is 5 parts by mass, and the pentaerythritol phosphate is 10 parts by mass, and the remaining steps and ingredients are the same as those in Example 2.

[0049] Effect example Polar oxygen index: The anti-aging and yellowing resistant foamed polyester materials prepared in the examples and comparative examples were prepared into samples with a size of 130 mm×10 mm×3 mm. The polar oxygen index was tested with an oxygen index tester from FTT Company of the United Kingdom in accordance with the GB / T 2406.2-2009 test standard.

[0050] Vertical combustion performance: The anti-aging and yellowing resistant foamed polyester materials prepared in the examples and comparative examples were prepared into samples with a size of 130 mm × 13 mm × 4 mm, and the vertical combustion performance was measured using a vertical combustion instrument of model UL94 of the British FTT Company in accordance with ASTM D3801-1996.

[0051] Apparent density: The apparent density of the anti-aging and yellowing resistant foamed polyester materials prepared in the examples and comparative examples was tested according to GB / T6343-1995.

[0052] Tensile strength: The anti-aging and yellowing resistant foamed polyester materials prepared in the examples and comparative examples were tested for tensile strength according to GB / T528-2009, using type 1 specimens at a tensile speed of 500 mm / min.

[0053] Compression permanent deformation: Take the anti-aging and yellowing resistant foamed polyester materials obtained in the embodiments and comparative examples and test the compression permanent deformation of the foamed materials according to GB / T10653-2001; the anti-aging and yellowing resistant foamed polyester materials obtained in the embodiments and comparative examples are processed into regular squares and stacked together to ensure that the thickness of the sample before compression is ≥25 mm, the side length is 50 mm±1 mm, and the thickness is 25 mm±1 mm. The test conditions are: the compression amount is controlled to be 30%, the temperature is 70°C±1°C, and the time is 22 h.

[0054] Anti-ultraviolet aging performance: The anti-aging and yellowing-resistant foamed polyester materials prepared in the examples and comparative examples were tested and calculated according to GB / T16422.3-2014 for 5 days after irradiation, and the tensile strength retention rate was calculated; tensile strength retention rate = (tensile strength after 5d aging) * 100% / tensile strength before aging.

[0055] Table 1 below shows the test results of various properties of the anti-aging and yellowing resistant foamed polyester materials prepared by using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.

[0056] Table 1 <![CDATA[Apparent density (g*cm -3 ).]]> Tensile strength (MPa) Compression set (%) Tensile strength retention rate (%) Limiting oxygen index (%) Vertical burning performance (UL-94) Example 1 0.674 14.32 13.42 91.2 30.2 V-1 Example 2 0.658 17.01 12.01 94.5 30.8 V-1 Example 3 0.669 16.65 13.23 92.4 30.6 V-1 Comparative Example 1 0.754 6.23 15.75 82.3 30.6 V-1 Comparative Example 2 0.806 5.75 16.54 85.2 30.1 V-1 Comparative Example 3 0.744 5.63 16.73 81.5 30.2 V-1 Comparative Example 4 0.813 6.32 17.22 91.4 27.2 V-2 Comparative Example 5 0.726 13.43 14.14 91.8 27.4 V-2 Comparative Example 6 0.889 5.52 19.22 86.4 27.2 V-2 Comparative Example 7 0.665 8.23 14.78 92.3 26.6 RT From Table 1, it can be found that the anti-aging and yellowing resistant foamed polyester material prepared in the embodiment has good foaming performance, mechanical properties, flame retardant properties and anti-ultraviolet aging performance; compared with comparative document 1, Example 2 found that the anti-oxidation SEBS prepared by unsaturated benzophenone ultraviolet absorber has good foaming performance, anti-ultraviolet aging performance and mechanical properties; compared with comparative document 2, Example 2 found that the anti-oxidation SEBS prepared by maleic anhydride has good foaming performance and mechanical properties; compared with comparative document 3, Example 2 found that the mechanical properties, anti-ultraviolet aging performance and foaming performance of the anti-aging and yellowing resistant foamed polyester material prepared by copolymerizing and grafting unsaturated benzophenone ultraviolet absorber, maleic anhydride and SEBS are good; compared with comparative example 4, Example 2 found that The flame retardancy, foaming and mechanical properties of the anti-aging and yellowing resistant foamed polyester material prepared by using carboxylated nano-silicon dioxide to prepare flame-retardant and wear-resistant filler are good; Example 2 is compared with Comparative Example 5 to find that the flame retardancy, foaming and mechanical properties of the anti-aging and yellowing resistant foamed polyester material prepared by mixing carboxylated nano-silicon dioxide, pentaerythritol and phosphorus oxychloride are good; Example 2 is compared with Comparative Example 6 to find that the mechanical properties, foaming properties, flame retardancy and anti-ultraviolet aging properties of the anti-aging and yellowing resistant foamed polyester material prepared by using anti-ultraviolet SEBS are good; Example 2 is compared with Comparative Example 7 to find that the mechanical properties, foaming properties and flame retardancy of the anti-aging and yellowing resistant foamed polyester material prepared by using flame retardant filler prepared by carboxylated nano-silicon dioxide are good.

[0057] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. An anti-aging and yellowing resistant foamed polyester material, characterized in that: The raw material components include, by weight: 3-5 parts of anti-ultraviolet SEBS, 3.6-7 parts of triethylamine, 4-6 parts of flame retardant and wear-resistant filler, 100 parts of TPEE, 0.9-1.1 parts of polymer wax, and 0.6-0.8 parts of foaming agent.

2. The anti-aging and yellowing resistant foamed polyester material according to claim 1, characterized in that: The anti-ultraviolet SEBS is obtained by copolymerization and grafting of an unsaturated benzophenone ultraviolet absorber, SEBS and maleic anhydride.

3. The anti-aging and yellowing resistant foamed polyester material according to claim 1, characterized in that: The flame retardant and wear resistant filler is obtained by mixing carboxylated nano silicon dioxide, pentaerythritol and phosphorus oxychloride.

4. The anti-aging and yellowing resistant foamed polyester material according to claim 1, characterized in that: The polymer wax is EVA wax.

5. The anti-aging and yellowing resistant foamed polyester material according to claim 1, characterized in that: The foaming agent is azodicarbonamide.

6. An anti-aging and yellowing resistant foamed polyester material as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: (1) Prepare the materials according to the following weight proportions: 3-5 parts of anti-ultraviolet SEBS, 3.6-7 parts of triethylamine, 2.5-3.5 parts of flame retardant and wear-resistant filler, 100 parts of TPEE, 0.9-1.1 parts of polymer wax, and 0.6-0.8 parts of foaming agent; (2) Under nitrogen protection, anti-ultraviolet SEBS and toluene were mixed in a mass ratio of 1:20-40, stirred at 500-900 rpm for 2-4 h, and then triethylamine and flame-retardant and wear-resistant fillers were added. Stirring was continued at 90 °C for 13-15 h, and the mixture was naturally cooled to room temperature and filtered. The mixture was washed with ethyl acetate and deionized water for 3-5 times in turn, and dried in a vacuum drying oven at 100 °C overnight to constant weight. The mixture was then placed in a high-speed mixer together with TPEE and EVA wax and stirred at 70 °C for 2-4 min. Then, azodicarbonamide, a foaming agent, was added, mixed evenly, and discharged. The mixture was then added to a single-screw extruder with a metering section temperature of 220-230 °C, a die temperature of 195 °C, and a screw speed of 60 rpm for extrusion. The mixture was cooled, pulled, and calendered into sheets.

7. The method for preparing the anti-aging and yellowing resistant foamed polyester material according to claim 6, characterized in that: The preparation method of the anti-ultraviolet SEBS is as follows: drying maleic anhydride in a vacuum drying oven at 120°C for more than 12 hours, first stirring and dissolving maleic anhydride, unsaturated benzophenone ultraviolet absorber, diisopropylbenzene peroxide, and acetone in a mass ratio of 1:1.2-1.4:0.09-0.11:10, and then evenly sprinkling on the surface of SEBS powder with a mass of 90-100 times that of maleic anhydride, and then putting it into a high-speed stirrer and stirring it at 1000-2000 rpm for 5 minutes, setting the stirring temperature to 80°C, and extruding it through a twin-screw extruder after mixing, with the temperatures of each zone of the extruder set to 220, 245, 265, 285, and 270°C, respectively, and the screw speed set to 40r / min.

8. The method for preparing the anti-aging and yellowing resistant foamed polyester material according to claim 7, characterized in that: The preparation method of the unsaturated benzophenone ultraviolet absorber is as follows: 1M / L sodium hydroxide aqueous solution and 2,4,4-trihydroxybenzophenone are mixed, and after being completely dissolved at 300-500rpm, they are subsequently stirred at 1200-1500rpm in an ice water bath, and acryloyl chloride is added dropwise, reacted for 1.5-2.5h, filtered, and the unsaturated benzophenone ultraviolet absorber is obtained; wherein the molar ratio of 2,4,4-trihydroxybenzophenone, acryloyl chloride, and sodium hydroxide is 1:0.9-1.1:

1.

9. The method for preparing the anti-aging and yellowing resistant foamed polyester material according to claim 6, characterized in that: The preparation method of the flame retardant and wear-resistant filler is as follows: dispersing carboxylated nano-silicon dioxide in toluene with a mass of 20 to 40 times, then adding pentaerythritol with a mass of 0.5 to 0.6 times the mass of the carboxyl group in the carboxylated nano-silicon dioxide, stirring at 300 to 500 rpm for 20 to 40 minutes, then adding concentrated sulfuric acid with a mass of 0.2 to 0.4 times the mass of the carboxylated nano-silicon dioxide, heating and refluxing for 2 to 4 hours, filtering, washing with acetone and deionized water for 2 to 4 times in sequence, and placing in an oven at 80°C. The mixture was dried in a vacuum oven for 48 hours, and then mixed with phosphorus oxychloride, wherein the molar ratio of pentaerythritol to phosphorus oxychloride was 1:6-6.

5. The mixture was heated to 80°C for reaction for 1.8-2.2 hours, and then heated to 110°C, and stirred at 1300-1700 rpm for reaction overnight until substantially no hydrogen chloride gas was generated. The mixture was then cooled to room temperature, filtered, and dried in a vacuum drying oven at 80°C to constant weight to obtain a flame retardant and wear resistant filler. During the filtration process, the mixture was washed with dichloromethane and ether for 3 times, respectively.

10. The method for preparing the anti-aging and yellowing resistant foamed polyester material according to claim 6, characterized in that: The preparation method of the carboxylated nano-silica is as follows: the nano-silica is ultrasonically dispersed in N,N-dimethylformamide with a mass of 20 to 40 times that of the nano-silica for 20 to 40 minutes, and then a KH550 hydrolyzate with a mass fraction of 6% is added, wherein the mass of the KH550 hydrolyzate is 1 to 2 times that of the nano-silica, and then the nano-silica is ultrasonically dispersed for 5 hours, and then poured into deionized water with a mass of 50 to 100 times that of the nano-silica, and the nano-silica is placed in a 120° C. oven for 24 hours, filtered, and dried in a 120° C. oven for 48 hours, and then naturally cooled to room temperature, and then dispersed in benzene with a mass of 40 to 60 times that of the nano-silica, and terephthalic acid with an equal mole of KH550 is added, and the temperature is raised to 85 to 95° C., and the nano-silica is ultrasonically dispersed for 1 to 2 hours, and then filtered, and washed with acetone and deionized water for 2 to 4 times, and dried in an 80° C. oven for 48 hours to obtain the carboxylated nano-silica.

Citation Information

Patent Citations

  • Formula of ultraviolet-resistant TPE (Thermoplastic Elastomer) plastics

    CN104371244A

  • Anti-aging TPE plastic formula

    CN104403253A

  • Environmental-friendly TPE (Thermo Plastics Elastomer) wire and cable material

    CN108017871A

  • Anti-ultraviolet heat-resistant PET (polyethylene terephthalate) film material as well as preparation method and application thereof

    CN117209979A

  • Preparation method of anti-ultraviolet and anti-yellowing polypropylene composite material

    CN118063888A

Cited By

  • Flame-retardant PVC (polyvinyl chloride) power tube and production process thereof

    CN119875265A